The Effectiveness of Manheim Peritonitis Index in Peritonitis Secondary to Hollow Viscous Perforation in Termso of Morbidity and Mortality - Almas Samo, Syed Nadeem Ali Shah, Naeem Mumtaz, Attaullah Arif, Haseena Rahman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Manheim peritonitis index (MPI) is the most effective scoring system in predicting morbidity and mortality in patients with peritonitis secondary to hollow viscus perforation. Higher score of MPI has higher morbidity in terms of prolong stay, wound sepsis, burst and re-burst, multiple explorations within same admissions, multi-organ dysfunction and failure. However, score less than 21 has better outcome in terms of uneventful recovery and timely discharge. Aim: To find out the effectiveness of MPI in terms of morbidity and mortality in patients with peritonitis secondary to hollow viscus perforation. Methods: This is a quantitative analytical cross sectional study carried out at a General surgical department and casualty surgical bay of a tertiary care hospital Lady Reading Hospital MTI, located in Khyber Pakhtunkhwa province of Pakistan, spanning a duration of six months from August 2021 to January 2022. MPI score was applied on all the patients with peritonitis secondary to hollow viscus perforation their scores and scores related morbidity and mortality was analyzed using chi-square test, P value kept less than 0.05. All the data entered on predesigned electronically Generated Questionnaire and analyzed through SPSS software 24 version. Results: Comorbid, age of patient, gender, nature of exudate, time of presentation, associated shock, organ failure was the most associated factors along with all scores of MPI affecting morbidity and mortality in our study. Amongst them Males (n=89) exceeded females (n=10). perforated duodenal ulcer was the most cause of hollow viscus perforation (n= 56), followed by enteric. Most of age group affected by enteric were younger age group ranging between 18y -25y. Higher score of MPI more than 21 have potential morbidity and mortality. The main findings in our study is higher MPI score has higher morbidity and mortality, age and co-morbid were additional factors which increases morbidity and mortality even if the MPI score was less than Conclusion: Manheim peritonitis index is a simple and effective tool when applied on patients with peritonitis secondary to hollow viscus perforation to predict morbidity and mortality. It should be routinely used for prediction of outcomes, focused strategy and treatment planning in patients with peritonitis secondary to hollow viscus perforation.